2020
DOI: 10.3390/molecules25184083
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Oligonucleotides Used to Identify Telomeric G-Quadruplexes in Metaphase Chromosomes and Fixed Cells by Fluorescence Lifetime Imaging Microscopy of o-BMVC Foci

Abstract: Identification of the existence of G-quadruplex (G4) structure, from a specific G-rich sequence in cells, is critical to the studies of structural biology and drug development. Accumulating evidence supports the existence of G4 structure in vivo. Particularly, time-gated fluorescence lifetime imaging microscopy (FLIM) of a G4 fluorescent probe, 3,6-bis(1-methyl-2-vinylpyridinium) carbazole diiodide (o-BMVC), was used to quantitatively measure the number of G4 foci, not only in different cell lines, but also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Based on the distinctive fluorescence lifetime response of G-Quadruplex, the content of DNA G-Quadruplex in lung, mammary and hepatic cancer cells is four times than that in normal cells, which can be exploited for cancer diagnosis [ 104 ]. Similarly, another G-Quadruplex fluorescent probe called o-BMVC foci, has also been used to identify G-Quadruplex motifs in combination with FLIM [ 105 ]. In addition to G-Quadruplex, the acetylation of histone lysine residues of acetyltransferase is another target for anti-cancer drugs that can be monitored by using a P300/CBP associated factor (PCAF) biosensor (HATS) in combination with FLIM (Fig.…”
Section: Flim Combined With Fluorophore Dye Probesmentioning
confidence: 99%
“…Based on the distinctive fluorescence lifetime response of G-Quadruplex, the content of DNA G-Quadruplex in lung, mammary and hepatic cancer cells is four times than that in normal cells, which can be exploited for cancer diagnosis [ 104 ]. Similarly, another G-Quadruplex fluorescent probe called o-BMVC foci, has also been used to identify G-Quadruplex motifs in combination with FLIM [ 105 ]. In addition to G-Quadruplex, the acetylation of histone lysine residues of acetyltransferase is another target for anti-cancer drugs that can be monitored by using a P300/CBP associated factor (PCAF) biosensor (HATS) in combination with FLIM (Fig.…”
Section: Flim Combined With Fluorophore Dye Probesmentioning
confidence: 99%
“…3). FLIM has been applied to quantitatively measure the number of G4 foci in metaphase chromosomes from number of cell lines showing that G4 structures are formed by human telomeric TTAGGG repeats on chromosomes (Tseng et al 2020). FLIM-FRET in vivo has shown that the concentration of polyvalent cations and ATP levels affect chromatin conformation and compaction.…”
Section: Introductionmentioning
confidence: 99%
“…The use of an antisense sequence was previously applied to unfold human telomeric G4 structures in vitro [ 27 , 28 ] and in vivo [ 29 ]. In the presence of antisense DNA, some of the unfolded species that formed as a result of thermal motion can be trapped as a stable duplex.…”
Section: Resultsmentioning
confidence: 99%